The economics of rebuilding fisheries : workshop proceedings. (OECD, 2010)
Rebuilding fisheries is a key challenge for many countries as some stocks are in a poor state while others are depleted. In May 2009, economists, biologists, fisheries managers and policy makers participated in an OECD Workshop on the Economics of Rebuilding Fisheries. The workshop was designed to identify and analyze economic uncertainties, policy issues, biological conditions and information constraints, and to review the role of key players in program delivery. This conference proceedings presents an overview of the major economic and institutional issues associated with rebuilding fisheries and provides examples of national and international initiatives.--Publisher's description.